Core–shell diodes for particle detectors. (14th January 2016) - Jia, Guobin; Plentz, Jonathan; Höger, Ingmar; Dellith, Jan; Dellith, Andrea; Falk, Fritz
Abstract: High performance particle detectors are needed for fundamental research in high energy physics in the exploration of the Higgs boson, dark matter, anti-matter, gravitational waves and proof of the standard model, which will extend the understanding of our Universe. Future particle detectors should have ultrahigh radiation hardness, low power consumption, high spatial resolution and fast signal response. Unfortunately, some of these properties are counter-influencing for the conventional silicon drift detectors (SDDs), so that they cannot be optimized simultaneously. In this paper, the main issues of conventional SDDs have been analyzed, and a novel core–shell detector design based on micro- and nano-structures etched into Si-wafers is proposed. It is expected to simultaneously reach ultrahigh radiation hardness, low power consumption, fast signal response and high spatial resolution down to the sub-micrometer range, which will probably meet the requirements for the most powerful particle accelerators in the near future. A prototype core–shell detector was fabricated using modern silicon nanotechnology and the functionality was tested using electron-beam-induced current measurements. Such a high performance detector will open many new applications in extreme radiation environments such as high energy physics, astrophysics, high resolution (bio-) imaging and crystallography, which will push these fields beyond their current boundaries.